Comparative sensitivity to zinc sulphate of Shigella isolates recovered from Nigerian children with low and marginal plasma zinc concentrations - Iwalokun, Bamidele Abiodun; Bakare, Senapon (Journal of Pediatric Infectious Diseases, 2008)
This study aims to determine the ability of zinc sulphate to inhibit growth of Shigella in vitro and test the hypothesis that the isolates recovered from Nigerian children with low plasma zinc concentration are more sensitive than the marginal plasma zinc isolates. The effect of zinc sulphate on extracellular protease secretion was also investigated. A total of 15 Shigella isolates recovered from the stool samples of 117 diarrheic children at various health centers in Lagos, Nigeria were tested for sensitivity to zinc sulphate in vitro by agar dilution method. Plasma zinc concentration was determined spectrophotometrically to enable stratification of the patients into two zinc arms: low (plasma zinc <9.2 μmol/L) and marginal (plasma zinc: 9.2–4 μmol/L). The in vitro effect of zinc sulphate on extracellular protease secretion based on azocasein hydrolysis in these isolates was also determined. Isolates of Shigella dysenteriae and Shigella flexneri were found to be more sensitive to zinc sulphate (minimum inhibitory concentration = 0.89–0.98 ± 0.03–0.06 mg/mL) than the isolates of Shigella sonnei and Shigella boydii (minimum inhibitory concentration = 1.13–1.4 ± 0.06–0.1 mg/mL (P < 0.05). The late logarithmic growth kinetics of these isolates also produced similar response to zinc sulphate in vitro. The observed zinc sulphate-induced growth inhibition of the Shigella isolates tested was further found to be associated with a decline in their extracellular protease secretion in both zinc arms. Zinc sulphate elicits in vitro inhibition of growth and serogroups-dependent decline in extracellular protease activity among Shigella isolates from Nigerian children irrespective of their systemic zinc levels. We conclude that zinc sulphate may have potentials to be used as a shigellocidal and anti-virulent agent in the management of shigellosis in children.
Keywords: Shigellosis; extracellular protease; zinc sulphate; growth inhibition